Social Participation: the construction of democracy in Brazilian health - doi:10.5020/18061230.2011.p266 - Cibelle Cristina da Silva Santos; Raquel Littério de Bastos (Universidade de Fortaleza, 2012)
Objective: To verify the theoretical construction of the terms "social participation" and "social control" relating them to the process of construction of democracy in Brazilian health. Methods: A bibliographic survey conducted in Lilacs and Scielo databases in the period of 2002 to 2009, using the following descriptors: Unified Health System (SUS), Participation and Social Control, Health Policy. Results: The post-1988 Constitution period brought the democratization and decentralization of social policy making room for countless experiences of popular participation. The SUS was created to meet the demands of the population in face of that historic moment. But today, more than twenty years of its creation, the lack of understanding of its guiding principles by health professionals and the population consists in a challenge to its effectiveness. Conclusions: Despite the institutionalization of participation, a culture of non-participation and the lack of knowledge of its instruments are significant barriers to the practice of social participation in health, which represents a complex work that needs to be developed with active Citizen-State relationship.